Effect of chemical stress and ultraviolet radiation in the bacterial communities of zebrafish embryos - Oliveira, Jacinta M. M. (2020)
This study aimed to assess the effect of ultraviolet radiation (UVR) and chemical stress (triclosan-TCS; potassium dichromate-PD; prochloraz-PCZ) on bacterial communities of zebrafish (Danio rerio) embryos (ZEBC). Embryos were exposed to two UVR intensities and two chemical concentrations not causing mortality or any developmental effect (equivalent to the No-Observed-Effect Concentration-NOEC; NOEC diluted by 10-NOEC/10). Effects on ZEBC were evaluated using denaturing gradient gel electrophoresis (DGGE) and interpreted considering structure, richness and diversity. ZEBC were affected by both stressors even at concentrations/doses not affecting the host-organism (survival/development). Yet, some stress-tolerant bacterial groups were revealed. The structure of the ZEBC was always affected, mainly due to xenobiotic presence. Richness and diversity decreased after exposure to NOEC of PD. Interactive effects occurred for TCS and UVR. Aquatic microbiota imbalance might have repercussions for the host/aquatic system, particularly in a realistic scenario/climate change perspective therefore, future ecotoxicological models should consider xenobiotics interactions with UVR.